Навчально-методичне забезпечення підготовки хористів парафіяльних храмів Київської єпархії в другій половині ХІХ ст - Перепелюк, Ольга (Naukovì zapiski. Serìâ: Ìstorìâ (Vìnnicʹkij deržavnij pedagogìčnij unìversitet ìmenì Mihajla Kocûbinsʹkogo), 2021)
The purpose of the article is to identify the historical processes that led to increased attention to the study of church singing in the second half of the nineteenth century and the analysis of methodological support for the training of future choristers of churches in parish schools. The methodological basis of the research is formed by general historical methods (analysis and synthesis), as well as the principles of scientificity, historicism, and objectivity. The scientific novelty lies in the fact that on the basis of the analysed publications of the church press and the available research of modern authors, for the first time, the recommendations that were provided to singing teachers for the preparation of future choristers are highlighted. The teaching aids and some methodological recomndations that were provided to facilitate the learning of students are indicated. Conclusions. In the ХІХ century, a number of reforms were carried out in all eparchies of the Russian Empire, concerning various spheres of spiritual education. There was a reorganization of educational institutions and an update of educational programs. The church singing became one of the main subjects; it was introduced for compulsory study in educational institutions of all levels – from academies to parish schools. Pupils of theological educational institutions mastered its theory and practice at the divine services. The Holy Synod issued provisions that regulated the volume of educational material and even a list of chants and prayers. In addition, church singing could be studied not for one semester or a year, but for the entire period of study. The main aspect requiring improvement in the reform process is the creation of church choirs. Since most of the teachers had a low level of solfeggio knowledge, they are not able to teach singers – teaching aids and methodological recommendations were developed to solve this problem. The useful information for singing teachers was distributed for giving the lesson: easy ways to study musical notation, elementary musical theory, examples of melodies, and so on. Their popularization was carried out with the help of church publications. The article analyses publications of the church press of the ХІХ century, as well as modern researches, which contains information on teaching church singing and advice for teachers who train children-choristers. Цель статьи заключается в определении исторических процессов, обусловивших повышенное внимание к изучению церковного пения во II половине XIX века и анализе методического обеспечения обучения будущих хористов храмов в церковноприходских школах. Методологическую основу исследования составляют общие исторические методы (анализа и синтеза), а также принципы научности, историзма и объективности. Научная новизна заключается в том, что на основе проанализированных публикаций церковной прессы и имеющихся исследований современных авторов впервые освещены рекомендации, которые предоставлялись учителям пения для подготовки будущих церковных певчих. Указываются учебные пособия и некоторые методические рекомендации, которые предусматривались для облегчения освоения материала учащимся. Выводы. В XIX веке во всех епархиях Русской империи был проведен ряд реформ, касающихся различных сфер духовного образования. Происходила реорганизация учебных заведений и обновление образовательных программ. Одним из главных учебных предметов стало церковное пение, оно было введено для обязательного изучения в учебных заведениях всех уровней – от академий до церковно-приходских школ. Воспитанники духовных учебных заведений овладевали им в теории и практически на богослужениях. Святейший Синод издавал положения, в которых регламентировался объем учебного материала и даже перечень песнопений и молитв. К тому же церковное пение могло изучаться не один семестр или год, а весь период обучения. Основным из направлений, требующий усовершенствования в процессе реформы – это создание церковных хоров. Поскольку большинство учителей имели низкий уровень знаний музыкальной грамоты и не способны научить певчих, были разработаны учебные пособия и методические рекомендации для решения этой проблемы. Распространялась полезная для учителей пения информация для проведения урока: легкие способы изучения нотной грамоты, элементарная музыкальная теория, примеры мелодий и тому подобное. Их популяризация осуществлялась с помощью церковных изданий. В статье проанализированы публикации церковной прессы ІІ половины XIX века, а также современные исследования, в которых содержится информация об обучении церковному пению и советы для учителей, осуществляющих подготовку детей-певчих. Мета статті полягає у визначенні історичних процесів, що обумовили підвищену увагу до вивчення церковного співу у ІІ половині ХІХ століття, та аналізі методичного забезпечення  навчання майбутніх хористів храмів у церковнопарафіяльних школах. Методологічну основу дослідження становлять загальні історичні методи (аналізу та синтезу), а також принципи науковості, історизму та об’єктивності. Наукова новизна полягає в тому, що на основі проаналізованих публікацій церковної преси та наявних досліджень сучасних авторів вперше висвітлено рекомендації, які надавалися учителям співу для підготовки майбутніх церковних півчих. Зазначаються навчальні посібники та деякі методичні рекомендації, які передбачалися для полегшення навчання учнів. Висновки. У ХІХ столітті в усіх єпархіях Російської імперії проведено ряд реформ, що стосувалися різних сфер духовної освіти. Відбувалася реорганізація навчальних закладів та оновлення освітніх програм. Одним із головних навчальних предметів став церковний спів, його введено для обов’язкового вивчення у навчальних закладах усіх рівнів – від академій до церковнопарафіяльних шкіл. Вихованці духовних навчальних закладів опановували його теоретично та практично на богослужіннях. Святійший Синод видавав положення, у яких регламентувався обсяг навчального матеріалу, і навіть перелік піснеспівів та молитов. До того ж церковний спів міг вивчатися не один семестр чи рік, а увесь період навчання. Основним із напрямів, який потребував удосконалення у процесі реформи, – створення церковних хорів. Оскільки більшість учителів мали низький рівень знань музичної грамоти або не здатні навчити півчих, то розроблено навчальні посібники та методичні рекомендації для вирішення цієї проблеми. Поширювалася корисна для учителів співу інформація для проведення уроку: легкі способи вивчення нотної грамоти, елементарна музична теорія, приклади мелодій тощо. Їх популяризація здійснювалася за допомогою церковних видань. У статті проаналізовано публікації церковної преси ХІХ століття, а також сучасні дослідження, у яких міститься інформація про навчання церковному співу та поради для учителів, які здійснюють підготовку дітей-півчих.